SERIOUS VIOLATIONS TO THE WOMEN RIGHT TO HEALTHCARE: THE CASE OF UNITED KINGDOM, ITALY AND UNITED STATES - Strapazzon, Carlos Luiz; Welter, Barbara (Unoesc International Legal Seminar, 2017)
This short paper has been prepared for the purpose of the violation of women's right to basic health care. It is an early work exclusively guided by the analysis of official documents of the United Nations. The source of research was the special committee on the elimination of all forms of discrimination against women. And the three developed countries report were analyzed: United Kingdom, Italy and the United States. The aim of this choice is relatively simple. The research, still in its initial phase, seeking to know which are the most frequent forms of violation of the right to women's health. And it seemed useful start the search from the knowledge of what is a violation of this right in countries that have the best tradition of respect for human rights. Further research should also address the case of Brazil and other similar countries, particularly those that are part of the BRICS.